2017
DOI: 10.3389/fmicb.2017.01013
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Food Additive Silica Nanoparticles and Food Matrices

Abstract: Nanoparticles (NPs) have been widely utilized in the food industry as additives with their beneficial characteristics, such as improving sensory property and processing suitability, enhancing functional and nutritional values, and extending shelf-life of foods. Silica is used as an anti-caking agent to improve flow property of powered ingredients and as a carrier for flavors or active compounds in food. Along with the rapid development of nanotechnology, the sizes of silica fall into nanoscale, thereby raising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 32 publications
0
38
1
Order By: Relevance
“…40 Recently, researchers have reported that interactions between food additive SiO 2 NPs and food matrices were highly dependent on the type of food component. 41 Moreover, the experimenters have suggested that toxicity of SiO 2 NPs depends on size, dose, and cell type. 42 Researchers have also demonstrated that the shape affected biodistribution, excretion, and toxicity of mesoporous SiO 2 NPs after oral and intravenous administration.…”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…40 Recently, researchers have reported that interactions between food additive SiO 2 NPs and food matrices were highly dependent on the type of food component. 41 Moreover, the experimenters have suggested that toxicity of SiO 2 NPs depends on size, dose, and cell type. 42 Researchers have also demonstrated that the shape affected biodistribution, excretion, and toxicity of mesoporous SiO 2 NPs after oral and intravenous administration.…”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…Although very much an overlooked exposure route, dietary sources of NMs make up approximately 16% of human Environmental Science: Nano Critical review exposures to NMs, compared to 58% and 25% for topical and inhalation exposure, respectively. 68,81 The high dietary exposure is typically through silica NMs which are used as a food additive (E551) and act as an anticaking agent. 81 Furthermore, nano silver is being used as an antimicrobial and in some cases as a (supposed) supplement in health foods, nano selenium is used as an additive in green tea products, nano iron is used to treat contaminated water or as a supplement, and a variety of metal oxides are used as colorants or may elute from packaging materials.…”
Section: Dietary Coronamentioning
confidence: 99%
“…68,81 The high dietary exposure is typically through silica NMs which are used as a food additive (E551) and act as an anticaking agent. 81 Furthermore, nano silver is being used as an antimicrobial and in some cases as a (supposed) supplement in health foods, nano selenium is used as an additive in green tea products, nano iron is used to treat contaminated water or as a supplement, and a variety of metal oxides are used as colorants or may elute from packaging materials. 82 Due to the diverse compositions of diets around the world each meal or item of food represents a complex mixture of a vast array of biomolecules such as proteins and metabolites from a range of plant and animal species, making the dietary-corona potentially the most complex and diverse corona relevant for human exposure.…”
Section: Dietary Coronamentioning
confidence: 99%
“…Nano fillers made up of silicate e.g. nylon clay hydrid and mess network of silicate are quite promising for safer manufacture of nano made packing material in food industry, however these NPs can mildly interact with food and toxicity studies are required to implement their use 24 . These packaging materials ensure quality of the food item by control oxidation, release active components and maintain the texture of food.…”
Section: How Safe Is Nano Particles Based Food Productsmentioning
confidence: 99%